A population approach using cholesterol imputation to identify adults with high cardiovascular risk: a report from AHRQ's EvidenceNow initiative. (29th November 2018) - Cykert, Samuel; DeWalt, Darren A; Weiner, Bryan J; Pignone, Michael; Fine, Jason; Kim, Jung In
Abstract: Objective: Large practice networks have access to EHR data that can be used to drive important improvements in population health. However, missing data often limit improvement efforts. Our goal was to determine the proportion of patients in a cohort of small primary care practices who lacked cholesterol data to calculate ASCVD risk scores and then gauge the extent that imputation can accurately identify individuals already at high risk. 219 practices enrolled. Patients between the ages of 40 and 79 years qualified for risk calculation. For patients who lacked cholesterol data, we measured the effect of employing a conservative estimation strategy using a total cholesterol of 170 mg/dl and HDL-cholesterol of 50 mg/dl in the ASCVD risk equation to identify patients with ≥ 10%, 10-year ASCVD risk who were eligible for risk reduction interventions then compared this to a rigorous formal imputation methodology. 345 440 patients, average age 58 years, qualified for risk scores. 108 515 patients were missing cholesterol information. Using the "good value" estimation methodology, 40 565 had risk scores ≥ 10% compared to 43 205 using formal imputation. However, the latter strategy yielded a lower specificity and higher false positive rate. Estimates using either strategy achieved ASCVD risk stratification quickly and accurately identified high risk patients who could benefit from intervention.